2019
DOI: 10.1186/s12864-019-5659-4
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide associations and functional gene analyses for endoparasite resistance in an endangered population of native German Black Pied cattle

Abstract: Background Gastrointestinal nematodes (GIN), liver flukes ( Fasciola hepatica ) and bovine lungworms ( Dictyocaulus viviparus ) are the most important parasitic agents in pastured dairy cattle. Endoparasite infections are associated with reduced milk production and detrimental impacts on female fertility, contributing to economic losses in affected farms. In quantitative-genetic studies, the heritabilities for GIN and F. hepatica … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 84 publications
(118 reference statements)
2
21
2
Order By: Relevance
“…BMP10 plays important roles in angiogenesis (Lei et al, 2016). ALCAM gene is reported to be involved in T-cell activation, development, inflammation and transendothelial migration of neutrophils (Weidle et al, 2010;May et al, 2019). In addition, we identified some candidate genes related to important economic traits.…”
Section: Discussionmentioning
confidence: 96%
“…BMP10 plays important roles in angiogenesis (Lei et al, 2016). ALCAM gene is reported to be involved in T-cell activation, development, inflammation and transendothelial migration of neutrophils (Weidle et al, 2010;May et al, 2019). In addition, we identified some candidate genes related to important economic traits.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, it is important to note that SNPs on chromosome 16, which is the genomic location of the MHC in the house sparrow, are not present on our 200k SNP array because of sequence assembly challenges directly related to the repetitive nature of the MHC gene family (Elgvin et al., 2017). Nevertheless, GWA analyses on raw or transformed faecal egg counts in livestock have frequently identified genes linked to adaptive and innate immunity, as well as diverse physiological processes, which indicates genes influencing infection intensity are distributed throughout the genome (Berton et al., 2017; May et al., 2019; Pickering et al., 2015; Psifidi et al., 2016; Silva et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Limitations apply to the GWAS approach when it is used to map pathogen resistance genes: success is more likely where resistance is due to common, large‐effect variants, and resistance genes identified in a given population may also depend on the genetic makeup of the pathogen community (MacPherson, Otto, & Nuismer, 2018). Despite these drawbacks, numerous genes relating to parasite resistance have been identified in livestock, including sheep (Benavides, Sonstegard, & Van Tassell, 2016; Berton et al., 2017; Periasamy et al., 2014; Pickering, Auvray, Dodds, & McEwan, 2015), cattle (May et al., 2019), goat (Silva et al., 2018; Zvinorova et al., 2016) and chicken (Boulton et al., 2018). GWAS on disease resistance traits in natural populations are limited.…”
Section: Introductionmentioning
confidence: 99%
“…So far, little is known about the genes affecting milk traits in DSN. Recently, genome-wide association studies (GWAS) in DSN for health traits identified three significant and two suggestive SNPs for clinical mastitis ( Meier et al, 2020 ) and 44 significant SNPs for endoparasite resistance ( May et al, 2019 ). Another study, investigating genomic variation in the casein gene cluster, found three protein variants of CSN2 and CSN3 and fixed protein variants for CSN1S1 and CSN1S2 ( Meier et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%